MPAS-Dev/MPAS-Analysis: v1.2.4 ... - Xylar Asay-Davis; Veneziani, Milena; Wolfram, Phillip J.; Roekel, Luke Van; Comeau, Darin; Brady, Riley; Kennedy, Joseph H; Gstreletz; Stephenprice; Turner, Adrian K.; , Kevin; Petersen, Mark; et al. (Zenodo, 2019)
Major Enhancements Add time series for Antarctic ocean regions #575 Add inset maps to transects and regional-mean plots #585 Add support for SOSE maps on a 10,000 x 10,000 km grid #597 Minor Enhancements Add MPAS-Analysis version and git hashtag to webpage #566 Add ncremap support to climatology depth slices and transects #557 Add climatology maps for min/max mixed-layer depth #574 Add subprocessCounts and daskTasks to ocean time series tasks #578 Allow zmin/zmax for ocean regions from config file #582 Update to nco>=4.8.1 #605 Clean-up Set gallery thumbnail sizes #560 Update most recent cori config file #580 clean-up related to climatologyMapMLDMinMax #579 Divide plotting module into 6 distinct modules #583 Several PRs to reduce memory cost of Read The Docs #588, #589, #590, #591, #592, #593, #594, #595 Add natural earth instructions to README for issues with downloading #606 Bug fixes Fix matplotlib version #564 Use chunking to reduce memory for Antarctic Melt time series #569 Fix linking of main and ...